Earth 2020 An Insider's Guide to a Rapidly Changing Planet - Tortell, Philippe (Open Book Publishers, 2020)
"Fifty years have passed since the first Earth Day, on 22 April 1970. This accessible, incisive and timely collection of essays brings together a diverse set of expert voices to examine how the Earth's environment has changed over this past half century, and what lies in store for our planet over the coming fifty years. Earth 2020: An Insider's Guide to a Rapidly Changing Planet responds to a public increasingly concerned about the deterioration of Earth's natural systems, offering readers a wealth of perspectives on our shared ecological past, and on the future trajectory of planet Earth. Written by world-leading thinkers on the front-lines of global change research and policy, this multi-disciplinary collection maintains a dual focus: some essays investigate specific facets of the physical Earth system, while others explore the social, legal and political dimensions shaping the human environmental footprint. In doing so, the essays collectively highlight the urgent need for collaboration across diverse domains of expertise in addressing one of the most significant challenges facing us today. Earth 2020 is essential reading for everyone seeking a deeper understanding of the past, present and future of our planet, and the role of humanity in shaping this trajectory."